Necronym as Cultural Identity in Batak Toba: An Anthroponymy Perspective - Simamora, Riris Mutiara Paulina; Datang, Frans Asisi; Yusuf, Munif; Erikha, Fajar (Journal of Cultural Analysis and Social Change, 2025)
This study explores the clan names in cemeteries, called necronyms, in Samosir Regency to identify the cultural identity of the Batak Toba people in Samosir Regency. Furthermore, the study explains the role of the boru clan name in cemeteries because the Batak Toba are known for their patrilineal system, which places men at the center of the lineage. The presence of the boru clan name is an interesting phenomenon requiring further investigation. This study used descriptive qualitative methods with data collection techniques in the form of interviews and documentation of the cemetery. Data sources were obtained from the clan names contained in Family Cards from the Samosir Civil Registry Office and the clan names contained in the cemetery. Data was analyzed using an anthroponomic approach in onomastics studies. The clan names from the family cards and cemetery were analyzed semantically based on etymology and presuppositional meanings. The results show that the cultural identity of the Batak Toba can be reflected in the clan names in the cemetery because they are in accordance with the character and personality of the community. Moreover, the dominant clan’s name in the family card does not necessarily dominate the clan names in the cemetery. The Batak Toba cultural identity in necronyms considers the boru clan names so that women are not completely ignored in the family tree. The boru clan names in the cemetery clarify the clan of the tulang or maternal brother. In terms of their meaning, the clan names in the cemetery are dominated by the etymological meaning of circumstances and the categorical meaning of activities. Additionally, the associative meaning of clan names in the cemetery is dominated by connotations of power and royalty. The emotive meaning of clan names in the cemetery is also predominantly positive, although some have negative connotations.